INTERACTION OF DNA WITH THE FOLDED AND UNFOLDED HISTONE HI IN THE PRESENCE OF SURFACE ACTIVE AGENTS (Journal of Sciences, Islamic Republic of Iran)
Interaction between DNA and histone H, was investigated in the presence and absence of sodium-n-dodecyl sulphate (SDS) and dodecyl trimethylammonium bromide (DTAB) at temperatures of 27 and 37?C, in 2.5 mM phosphate buffer, pH 6.4 by UV spectrophotometry, equilibriumdialysis and titration. The presence of 1.33 mM SDS caused histone H to fold and to further contact DNA. Binding data were used in the Wyman theoretical model to calculate the free energy and enthalpy of the interaction and were compared with equilibrium state. All data confirm the higher compaction for DNA in the presence of folded histone H (H in the presence of 1.33 mM SDS) relative to native histone H (H in the absence of SDS)